(untitled) (Research, Society and Development, 2020)
The use of okra mucilage as an alternative for adding value in tomato sauce was evaluated, acting as a thickening agent in natura and lyophilized form. The mucilage was extracted from okra and lyophilized, being characterized in terms of yield, functional, physical-chemical, bioactive, colorimetric and sensory properties. They were used in the formulation of tomato sauces in three formulations, one without mucilage (control) and two with moist and lyophilized mucilage. The okra mucilage showed an extraction yield of 53.87% and, when lyophilized, 1.67%, with a higher concentration of proteins, sugars and total soluble solids in relation to fresh okra and wet mucilage. Potential water and oil retention capacity was observed in lyophilized mucilage. Tomato sauces showed significant amounts of total phenolics and high antioxidant activity, with 27.37 eq. trolox mg/100g of the sauce with lyophilized mucilage, tending to orange. With hygienic-sanitary conditions suitable for consumption, the sauces showed good sensory acceptance, acceptability indexes and purchase intention. The product with lyophilized mucilage stood out in the attributes consistency, flavor and overall impression, being the preferred formulation by the judges, described as uniform, soft, smooth in appearance, pleasant and moist flavor. The tomato sauce with lyophilized mucilage showed positive values for the attributes uniform appearance, soft, smooth, homogeneous appearance, pleasant and moist flavor. Thus, the use of okra mucilage as a natural additive, especially in lyophilized form, may be viable in tomato sauce, acting as a thickener and emulsifier by benefiting the functional, bioactive and sensory characteristics.